P2P networking and applications - Koegel Buford, John F.; Yu, Hong Heather coautor; Lua, Eng Keong coautor (Burlington: Morgan Kaufmann, 2009)
Ch1: Introduction Ch2: Peer-to-Peer Concepts Ch3: Unstructured Overlays Ch4: Structured Overlays-Geometry and Routing Ch5: Overlay Dynamics Ch6: Peer-to-Peer in Practice Ch7: Search Ch8: Peer-to-Peer Content Delivery Ch9: Peercasting and Overlay Multicasting Ch10: Measurement Ch11: Service Overlays Ch12: Voice over Peer-to-Peer Ch13: Mobility Ch14: Security Ch15: Managed Overlays